Effectiveness of vaginal breech birth training strategies: An integrative review of the literature. Issue 2 (17th February 2017) - Walker, Shawn; Breslin, Eamonn; Scamell, Mandie; Parker, Pam
Abstract: Background: The safety of vaginal breech birth depends on the skill of the attendant. The objective of this review was to identify, synthesize, and report the findings of evaluated breech birth training strategies. Methods: A systematic search of the following on‐line databases: Medline, CINAHL Plus, PsychINFO, EBM Reviews/Cochrane Library, EMBASE, Maternity and Infant Care, and Pubmed, using a structured search strategy. Studies were included in the review if they evaluated the efficacy of a breech birth training program or particular strategies, including obstetric emergency training evaluations that reported differentiated outcomes for breech. Out of 1040 original citings, 303 full‐text articles were assessed for eligibility, and 17 methodologically diverse studies met the inclusion criteria. A data collection form was used to extract relevant information. Data were synthesized, using an evaluation levels framework, including reaction, learning (subjective and objective assessment), and behavioral change. Results: No evaluations included clinical outcome data. Improvements in self‐assessed skill and confidence were not associated with improvements in objective assessments or behavioral change. Inclusion of breech birth as part of an obstetric emergencies training package without support in practice was negatively associated with subsequent attendance at vaginal breech births. Conclusions: As a result of the heterogeneity of the studies available, and the lack of evidence concerning neonatal or maternal outcomes, no conclusive practice recommendations can be made. However, the studies reviewed suggest that vaginal breech birth training may be enhanced by reflection, repetition, and experienced clinical support in practice. Further evaluation studies should prioritize clinical outcome data.